2022
DOI: 10.3847/psj/ac4d9c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Distribution of Organic Carbon and Nitrogen in Impact Crater Melt on Titan

Abstract: Titan is a chemically rich world that provides a natural laboratory for the study of the origin of life. Titan’s atmospherically derived C x H y N z molecules have been shown to form amino acids when mixed with liquid water, but the transition from prebiotic chemistry to the origin of life is not well understood. Investigating this prebiotic environment on Titan is one of the primary motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…Actively erupting water vapor plumes have been identified on Europa (Huybrighs et al., 2020; Jia et al., 2018; Roth et al., 2014; Sparks et al., 2017), and impact melt chambers beneath Manannán Crater have been proposed as a potential source (Steinbrügge et al., 2020). Previous models of impact‐induced cryovolcanism, and post‐impact melt chambers more generally, assume that once formed the melt remains static within the ice (Bowling et al., 2018; Fagents, 2003; Fagents et al., 2000; Hedgepeth et al., 2022; Hesse & Castillo‐Rogez, 2019; Lesage et al., 2020; Quick et al., 2019; Steinbrügge et al., 2020). Our simulations suggest that in many cases this is a flawed assumption and that viscous deformation is an important aspect of the evolution of impact melts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actively erupting water vapor plumes have been identified on Europa (Huybrighs et al., 2020; Jia et al., 2018; Roth et al., 2014; Sparks et al., 2017), and impact melt chambers beneath Manannán Crater have been proposed as a potential source (Steinbrügge et al., 2020). Previous models of impact‐induced cryovolcanism, and post‐impact melt chambers more generally, assume that once formed the melt remains static within the ice (Bowling et al., 2018; Fagents, 2003; Fagents et al., 2000; Hedgepeth et al., 2022; Hesse & Castillo‐Rogez, 2019; Lesage et al., 2020; Quick et al., 2019; Steinbrügge et al., 2020). Our simulations suggest that in many cases this is a flawed assumption and that viscous deformation is an important aspect of the evolution of impact melts.…”
Section: Discussionmentioning
confidence: 99%
“…Many non‐penetrating impacts generate large melt chambers, which are presently thought to sustain long‐lived cryovolcanism, for example, Manannán Crater on Europa (Steinbrügge et al., 2020) or Occator Crater on Ceres (Bowling et al., 2018; Hesse & Castillo‐Rogez, 2019; Quick et al., 2019; Raymond et al., 2020). Models for the evolution of such impact‐induced melt chambers assume that they freeze in place, which implicitly assumes the surrounding ice is rigid (Bowling et al., 2018; Fagents, 2003; Fagents et al., 2000; Hedgepeth et al., 2022; Hesse & Castillo‐Rogez, 2019; Lesage et al., 2020; Quick et al., 2019; Steinbrügge et al., 2020). However, impacts that generate melt chambers also significantly warm and soften the surrounding ice making it susceptible to viscous deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these deposits may last for tens of thousands of years before freezing completely. These timescales are much longer than those calculated by Hedgepeth et al (2022) for a melt pool a few hundred meters thick, who found that it takes just a few hundred years to freeze such melt pools. These estimates for meltpool depth came from previous modeling work, which assumed impact into cold water ice.…”
Section: Discussionmentioning
confidence: 75%
“…This would increase the likelihood of the formation of complex organics on Titan. These molecules would then concentrate within the melt sheet at different depths (Hedgepeth et al 2022). If these melt sheets are later eroded by fluvial processes, exposing these layers, Dragonfly may be able to detect the prebiotic species formed there (Neish et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The Burney group, dating back to Pluto's earliest high-impact era, extends from the north pole down into Cthulhu Macula (Schenk et al 2018;Singer et al 2021;White et al 2021). Cthulhu Macula stands out with its uniquely low-albedo surface due to a covering of organic particles (Sagan & Khare 1979;Neish et al 2010;Grundy et al 2018;Neish et al 2018;Cruikshank et al 2019aCruikshank et al , 2021Lorenz et al 2021;Hedgepeth et al 2022). The polar uplands, in contrast, bear signs of obliquity-driven cycling of methane (i.e., erosion and deposition) that likely influences their crater topography, even though the methane layer there is currently thin (Binzel et al 2017;Forget et al 2017;Howard et al 2017b;Protopapa et al 2017;Earle et al 2018;Earle et al 2022).…”
Section: Geologic Historymentioning
confidence: 99%